The authority of the Caliph and the limits of his mandate in the Islamic political system - bouhali, mohammed; bendaas, djamel (Journal of Social Sciences and Humanities, 2025)
The subject of the Khalifa’s authority and the limits of his mandate in the Islamic political system is one of the topics that political jurisprudence has been interested in, both ancient and modern, because it relates to the most important position in the state and its powers represented in the powers entrusted to him. Political jurisprudence, ancient and modern, has highlighted those powers, which relate to executive and judicial powers. It is noted that there are those who presented those powers mixed between religious and worldly powers, and there are those who tried to distinguish between them, i.e. religious powers and political powers, but this division is only for the sake of distinction and highlighting powers and its purpose is not to separate what is religious and worldly, but rather it is distinction. Religious powers were not intended to preserve and protect the foundations of Islam, such as protecting the faith, fighting enemies, and performing the rituals of religion. As for the political powers, which political jurisprudence expressed as worldly powers, they are what falls within the rules of the executive authority, such as maintaining internal and external security, administrative, financial and judicial affairs. As for the legislative powers, and given the nature of this authority in Islam, the Imam has the authority Legislation if it is based on diligence, and if jurisprudence differs regarding the extent to which the Imam can compel the legal rulings based on diligence, then the most likely opinion is that it is compulsory, and this is out of concern for preserving the legal laws and guarding the religious rulings and not leaving them in chaos, and the guardian of the matter is nevertheless bound by restrictions, which are commitment to the principle of consultation, and commitment to the opinion of the majority, and in view of the khalifa’s powers and authority, Islamic law has set limits and guarantees so that the Imam does not exceed the limits of his authority, and these are represented in commitment to consultation, and supervision over it, which results in responsibility in the event that those limits are exceeded.